2019
DOI: 10.1007/s00167-019-05368-8
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of an anatomic trochlear-cutting patellofemoral arthroplasty: patient selection is key

Abstract: Purpose The purpose of this study was to report outcomes of a recent anatomic trochlear‐cutting patellofemoral arthroplasty (PFA) system at > 3 years. The hypothesis was that its functional scores and revision rates would be at least equivalent to those reported for other ‘trochlear‐cutting’ implants in the literature. Methods Twenty‐eight consecutive patients that had received PFA using the same anatomic trochlear‐cutting implant (KneeTech PFJ, Corin‐Tornier, Montbonnot, France) with a dome‐shaped patellar bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Early (stage 1–2 according to Iwano classification) isolated primary PFOA results are often refractory to the conservative treatment (physiotherapy, intraarticular viscosupplementation, and/or PRP), whereas nonreplacement surgery (arthroscopic debridement with or without lateral release, chondroplasty, lateral facetectomy) results are often ineffective in patients with moderate (stage 3) isolated primary PFOA. Certainly, in all those patients, arthroplasty surgery [patellofemoral arthroplasty (PFA) or total knee arthroplasty (TKA)] appears premature and is reserved for patients with severe (stage 4) PFOA [ 8 , 9 , 33 ]. The 23 patients of this study presented early (70%) or moderate (30%) PFOA, whereas none of the patients presented a stage 4 (bone-on-bone) patellofemoral degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Early (stage 1–2 according to Iwano classification) isolated primary PFOA results are often refractory to the conservative treatment (physiotherapy, intraarticular viscosupplementation, and/or PRP), whereas nonreplacement surgery (arthroscopic debridement with or without lateral release, chondroplasty, lateral facetectomy) results are often ineffective in patients with moderate (stage 3) isolated primary PFOA. Certainly, in all those patients, arthroplasty surgery [patellofemoral arthroplasty (PFA) or total knee arthroplasty (TKA)] appears premature and is reserved for patients with severe (stage 4) PFOA [ 8 , 9 , 33 ]. The 23 patients of this study presented early (70%) or moderate (30%) PFOA, whereas none of the patients presented a stage 4 (bone-on-bone) patellofemoral degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third generation PFA are reported to have satisfactory patient reported and functional outcomes and reduction in mechanical complications [ 2 , 4 , 11 , 28 ].…”
Section: Designsmentioning
confidence: 99%
“…A recent study showed similar patient-reported outcomes after second-generation PFJR and TKA if patients were selected appropriately [ 74 ]. Dejour et al [ 75 ] postulated that early revision surgeries due to OA progression only occurred when patients were selected improperly. They also showed that PFJR should be restricted to patients that developed patellofemoral OA due to instability or maltracking of the patella and that it should not be used in patients with degenerative patellofemoral OA.…”
Section: Focal Chondral Defects and Patellofemoral Joint Replacementmentioning
confidence: 99%